Bland–Altman plot to assess the consistency of arterial and venous blood lactate in the emergency room: a retrospective cohort study - Yongkai Li; Xiaojing He; Dandan Li; Xin Yuan; Jun Xu; Jianzhong Yang (Scientific Reports)
Abstract To measure the correlation and agreement between arterial and peripheral venous blood lactate in the emergency room and to assess the predictive value of lactate for the occurrence of cardiac arrest. This was a retrospective cohort study involving 784 patients from January 1, 2020, to July 31, 2021, in the Emergency Room of the First Affiliated Hospital of Xinjiang Medical University. General information, vital signs, clinical symptoms, and laboratory findings of the patient were collected. Linear regression was used to analyze the correlation between arterial and venous blood lactate, Bland–Altman plots were drawn to assess the concordance of (arterial-venous) serum lactate concentrations, and the predictive value of arterial and venous lactate for the occurrence of cardiac arrest was assessed by using the receiver operating characteristic curve (ROC). A total of 784 emergency room patients were included in the study, of whom 384 experienced cardiac arrest and 400 had no cardiac arrest. Arterial and venous lactate univariate linear regression analysis, correlation coefficient r = 0.80, linear equation Y(venous blood lactate) = 0.729 + 0.960*X(arterial blood lactate), and had statistical significance (P < 0.001); arterial blood (lactate) and venous blood (lactate) were -0.548 (95%CI -0.774 ~ -0.322 mmol/L), and the upper and lower limits of the 95% limits of agreement (LoA) were 5.777 (95%CI 5.390 ~ 6.163 mmol/L) and -6.872 (-7.2590 ~ -6.4855 mmol/L), indicating that the consistency of arterial blood lactate and venous blood lactate is poor and statistically significant (P < 0.001). The results of this study show that venous and arterial blood lactate levels are not identical, but are highly correlated and are important predictors of cardiac arrest in emergency room patients.